Capacity Assessment of the Sewage Treatment plant at the Residency Complex / Al- Dour / salah Al-Deen - Buraq Mahmoud Atta; Badran Adnan Saeed; Hutaf Abdul-Malik Ahmed (Tikrit Journal of Pure Science, 2023)
The efficiency of the waste water treatment plant at Salah Al-deen governorate was evaluated by measuring certain physical and chemical properties. The results showed that water temperature rates (19.840C), electric conductivity (544.2 Micro Siemens/cm), pH (7.76), biological oxygen demand (40.3 mg/L.) and chloride ion concentration (209.16 mg/ L.) in drained water were accordance the Iraqi standard properties determinants. Turbidity (7.9 naphthalene turbidity unit), total hardness (396.8 mg calcium carbonate /L.), and magnesium hardness (194.3 mg magncium carbonate /L.) were removed efficiently by the station, as the removal capacity of these determinants where (93.404%), (2.935%) and (15.337) respectively. The station was not capable enough to remove the calcium hardness (202.80mg calcium carbonate/L.) and total alkalinity (345.2 mg calcium carbonate/L (. The statistical analysis of the studied factors in the station have no significant differences among the studded sites and have highly significant differences among the studded months.